Babies born before arrival to hospital and maternity unit closures in Queensland and Australia. Issue 3 (September 2015) - Kildea, Sue; McGhie, Alexandra C.; Gao, Yu; Rumbold, Alice; Rolfe, Margaret
Abstract: Background: Evidence suggests the closure of maternity units is associated with an increase in babies born before arrival (BBA). Aim: To explore the association between the number of maternity units in Australia and Queensland by birthing numbers, BBA rate and geographic remoteness of the health district where the mother lives. Methods: A retrospective study utilised routinely collected perinatal data (1992–2011). Pearson correlation tested the relationship between BBA rate and number of maternity units. Linear regression examined this association over time. Findings: During 1992–2011, the absolute numbers ( N = 22, 814) of women having a BBA each year in Australia increased by 47% ( N = 836–1233); and 206% ( n = 140–429) in Queensland. This coincided with a 41% reduction in maternity units in Australia ( N = 623–368 = 18 per year) and a 28% reduction in Queensland ( n = 129–93). BBA rates increased significantly across Australia, r = 0.837, n = 20 years, p < 0.001 and Queensland, r = 0.917, n = 20 years, p < 0.001 and this was negatively correlated with the number of maternity units in Australia, r = −0.804, n = 19 years, p < 0.001 and Queensland, r = −0.906, n = 19 years, p < 0.001. Conclusions: The closure of maternity units over a 20-year period across Australia and Queensland is significantly associated with increased BBA rates. The distribution is not limited to rural and remote areas. Given the high risk of adverse maternal and neonatal outcomes associated with BBA, it is time to revisit the closure of units.